Protease-Activated Receptors in the Intestine: Focus on Inflammation and Cancer - Sébert, Morgane; Sola-Tapias, Nuria; Mas, Emmanuel; Barreau, Frédérick; Ferrand, Audrey (Frontiers in Endocrinology, 2019)
Protease-activated receptors (PARs) belong to the G protein-coupled receptor (GPCR) family. Compared to others GPCRs, the specificity of the four PARs is the lack of physiologically soluble ligands. Indeed, PARs are physiologically activated after proteolytic cleavage of their N-terminal domain by proteases. The resulting N-terminal end becomes a tethered activation ligand that interact with the extracellular loop 2 domain and thus induce PAR signal. PARs expression is ubiquitous and these receptors have been largely described in chronic inflammatory diseases and cancer. In this review, after describing their discovery, structure, mechanisms of activation, we then focus on the roles of PARs in the intestine and the two main diseases affecting the organ, namely inflammatory bowel disease and cancer.